Hubungan status gizi dengan kualitas tidur pada mahasiswa fakultas kedokteran ukrida angkatan 2021 - Sutanto, Jovian Christopher; Hartanto, Hartanto; Yen, Liauw Djai (Universitas Kristen Krida Wacana, 2025)
Good sleep quality is a crucial aspect of maintaining physical and mental health. This study aims to analyze the relationship between nutritional status and sleep quality among adolescents. The research employed a quantitative design with a purposive sampling method, involving 143 respondents. Nutritional status was measured using Body Mass Index (BMI) based on the Asia-Pacific standard, while sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Data analysis was conducted using the chi-square test to examine the relationship between these variables. The results revealed a significant relationship between nutritional status and sleep quality among the respondents p=0,00 (p < 0.05). Adolescents with overweight status tended to have poorer sleep quality compared to those with normal nutritional status. These findings highlight the importance of maintaining optimal nutritional status to improve sleep quality in adolescents.